CROSS-RELIGIOUS ADOPTION OF ISLAMIC FINANCIAL TECHNOLOGY AND FINANCIAL LITERACY: A SYSTEMATIC LITERATURE REVIEW - Ismul Aksan; Muhsin N Bailusy; Filipus Argentano Guntur Suryaputra (Universitas Nusa Cendana, 2026)
This systematic review explores the intersection of Islamic Financial Technology (FinTech) and financial literacy, analyzing 27 scholarly publications from 2018 to 2024. The review employed a rigorous methodology, utilizing databases such as Scopus and tools like Publish or Perish (PoP) and VOSViewer for bibliometric network analysis. The findings reveal a notable shift towards high-impact journals (Q1 and Q2), with a significant increase in publication volume in 2024. Geographically, Indonesia, India, and Malaysia are the major contributors, though many Indonesian studies are non-quartile, indicating potential for quality enhancement. Thematic analysis highlights the predominance of user adoption studies, with key theories like the Technology Acceptance Model (TAM), Unified Theory of Acceptance and Use of Technology (UTAUT), and Theory of Planned Behavior (TPB) applied to understand the factors influencing Islamic FinTech adoption. Despite these contributions, gaps in the literature persist, particularly regarding non-Muslim perspectives, tailored financial literacy programs, and the integration of emerging technologies like blockchain and AI. This review identifies these research gaps and provides recommendations for future studies, emphasizing the need for longitudinal research and technological innovation to advance the field of Islamic FinTech and financial literacy